Strength Analysis of a Ducted Axial Fan Blade - Marek ROŚKOWICZ; Ryszard CHACHURSKI; Sławomir TKACZUK; Piotr LESZCZYŃSKI; Maciej MAJCHER; Łukasz OMEN (Problemy Mechatroniki)
This paper presents a numerical strength analysis of a ducted axial fan blade. Ducted axial fans are a large group of fluid-flow machines. The analysis was designed to determine the causes of cyclic failures of a ventilation unit. The paper presents a reverse engineering approach to the mapping of the fan blade’s geometrical features. The geometrical features were mapped by triangulation from the scanning images produced by a 3D optical scanner. These were followed by simplifying assumptions on which the numerical calculations were based. The numerical calculations were carried out at the operating rotational speeds of the ducted axial fan’s rotor. The course of the numerical calculations is described, and their results are also presented herein. The results are represented on colour maps of stress distribution for selected structural elements of the fan blade. The stress distribution at a blade cross-section was compared to CT scans of the fractures of failed rotor blade airfoils. Final conclusions were developed which show that the design engineering process of fans should feature optimisation of the fan’s efficiency, including the strength and performance parameters, which should include the service life of the fan.